Optimalisasi Strategi Marketing 5.0 dalam Kewirausahaan Budidaya Jamur Tiram Berbasis Prinsip Ekonomi Syariah di Nasyiatul Aisyiyah Cabang Pahandut Kota Palangka Raya: Optimizing Marketing 5.0 Strategy in Oyster Mushroom Cultivation Based on Sharia Economic Principles at Nasyiatul Aisyiyah, Pahandut Branch, Palangka Raya City - Annisa, Nur; Hasanah, Muqor Rama; Aufa, Mohamad Nor; Nurkhaliza, Gusti Nida (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
This community service activity aims to transfer knowledge on oyster mushroom entrepreneurship, integrated with Sharia Economic Principles and Marketing Strategy 5.0, to the cadres of Nasyiatul Aisyiyah Pahandut Branch, Palangka Raya City, an autonomous Muhammadiyah organization consisting of young women, as initial capital for modern and ethical business ideas. The activity was carried out through intensive one-day training using the Participatory Action Research model, which focused on the simultaneous integration of three domains of knowledge: cultivation production techniques, Sharia business ethics, and digital marketing. The target of the activity was to build an entrepreneurial mindset in a community with no prior business background. The results of competency measurements, comparing pre-test and post-test, showed an average increase of 66.3%, with the highest increase in the Marketing Strategy 5.0 domain (90.1%). This increase confirms the effectiveness of the knowledge integration model in a short time. This service concludes that the integrated training model that presents holistic, ethical business ideas (technically, ethically, and digitally ready) has achieved the goals of education and entrepreneurial empowerment very well, providing a sustainable business blueprint for the young women's community.